Automatic proof-search heuristics in the Maude invariant analyzer tool - Rocha, Camilo (Switzerland, 2013)
The Invariant Analyzer Tool is an interactive tool that mechanizes an inference system for proving safety properties of concurrent systems, which may be infinite-state or whose set of initial states may be infinite. This paper presents the automatic proof-search heuristics at the core of the Maude Invariant Analyzer Tool, which provide a substantial degree of automation and can automatically discharge many proof obligations without user intervention. These heuristics can take advantage of equationally defined equality predicates and include rewriting, narrowing, and SMT-based proof-search techniques.

La herramienta Invariant Analyzer es una herramienta interactiva que mecaniza un sistema de inferencia para probar las propiedades de seguridad de sistemas concurrentes, que pueden ser de estado infinito o cuyo conjunto de estados iniciales puede ser infinito. Este documento presenta las heurísticas de búsqueda automática de pruebas en el núcleo de la herramienta Maude Invariant Analyzer, que proporciona un grado sustancial de automatización y puede cumplir automáticamente muchas obligaciones de prueba sin la intervención del usuario. Estas heurísticas pueden aprovechar los predicados de igualdad definidos ecuacionalmente e incluyen técnicas de reescritura, estrechamiento y búsqueda de pruebas basadas en SMT.
Keywords: computability; concurrency control; human computer interaction; inference mechanisms; interactive systems; program verification; rewriting systems; theorem proving; Modelos matemáticos; Modelado orientado a objetos; Sistemas interactivos (computadores); Sistemas de reescritura; Maude Invariant Analyzer; SMT; Safety; Equations; Mathematical model; Cognition; Algebra; Discharges (electric); Object oriented modeling